The influence of perceived stress and self-control on efficacy of repeated transcranial direct current stimulation in non-treatment-seeking smokers. (1st September 2021) - Müller, Tobias; Shevchenko, Yury; Gerhardt, Sarah; Kiefer, Falk; Vollstädt-Klein, Sabine
Highlights: TDCS had no beneficial effect on consumption, craving, or executive functions. Light smokers might be more responsive to the placebo effect. Heavy smokers might benefit more from specific effects of tDCS. Low levels of self-control might have a positive influence on tDCS. High levels of perceived stress might enhance the effects of tDCS. Abstract: Introduction: Transcranial direct current stimulation (tDCS) has recently been raising interest in its therapeutic impact on tobacco use disorder. This study investigates the effects of repeated frontal tDCS (anode: F3, cathode: F4) on cigarette consumption, craving and executive functions. Material and methods: In a randomized sham-controlled trial, 24 individuals received active (2.0 mA) and 20 individuals received sham stimulation (0.3 mA) for 20 min on five consecutive days. The participants indicated their tobacco cravings, answered questionnaires and completed neuropsychological tasks at various time points throughout the study. Carbon monoxide (CO) levels and the daily numbers of consumed cigarettes were recorded. Results: Both intervention groups experienced a significant decrease in the daily number of smoked cigarettes, CO levels, and craving after the stimulation, however, there were no improvements in executive functions. These results did not differ significantly between both intervention groups. Additionally, in the active group, a higher level of perceived stress and a lower level of self-control were linked to a lower cigarette consumption, respectively a higher reduction of the level of CO. Conclusion: This study does not support the hypotheses that tDCS reduces cigarette consumption, attenuates substance craving, or improves executive functions beyond the placebo effect. Our subgroup analysis suggests that high levels of perceived stress and low self-control may be predictors for a successful reduction in cigarette consumption. Furthermore, the placebo effect might be rather high for light smokers, whereas heavy smokers seem to benefit more from the specific effects of tDCS. Clinical trial registration number: NCT03691805